OPTIMIZATION OF CONDITION FOR METHYLEN BLUE ADSORPTION USING ACTIVATED COMMERCIAL ZEOLITE - Wijayanti (Politeknik ATK Yogyakarta, 2024)
Dye is the one of the industrial waste which is not degraded easily in the environment. Methylen blue is a dye that is often used in industries and can be an environmental pollution. Adsorption is used in this research to solve the problem. This study used an activated commercial zeolite. The adsorption conditions were optimized based on adsorbent mass, contact time, and the initial concentration of adsorbate. The results showed that the optimum condition was using 3 grams of adsorbents with contact time of 60 minutes and initial concentration of adsorbate not more than 125 mg/L. This adsorption followed pseudo-second order kinetic model and Freundlich isoterm model.